2021
DOI: 10.1002/ece3.7776
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic restriction of plant invasion in drought‐stressed environments: Implications for insect‐pollinated plant communities in water‐limited ecosystems

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 90 publications
1
5
0
Order By: Relevance
“…This result is consistent with past work showing that insects can increase their visitation to non-native flowers when they are relatively more available (e.g., Salisbury et al, 2015). Our results also support previous work done in this system (Simon et al, 2021) and in others (Gerlach & Rice, 2003;Pearson et al, 2012) showing that non-native plants flower later in the season than native plants. However, given that our work is based on a single year, future studies could determine whether the patterns we observed here are sensitive to interannual variability (e.g., weather, population dynamics).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This result is consistent with past work showing that insects can increase their visitation to non-native flowers when they are relatively more available (e.g., Salisbury et al, 2015). Our results also support previous work done in this system (Simon et al, 2021) and in others (Gerlach & Rice, 2003;Pearson et al, 2012) showing that non-native plants flower later in the season than native plants. However, given that our work is based on a single year, future studies could determine whether the patterns we observed here are sensitive to interannual variability (e.g., weather, population dynamics).…”
Section: Discussionsupporting
confidence: 93%
“…Since late‐season plant community dynamics in Garry oak savannas and other Mediterranean‐like ecosystems are driven by drought (Klassen et al, 2015), flowering later than natives could be a result of increased drought tolerance in certain non‐native plant species. For instance, in this system, non‐native floral area was found to be negatively correlated with soil moisture (Simon et al, 2021). Since historical data on flowering times in Garry oak savannas are unavailable, it is unknown whether non‐native plants are occupying vacant temporal niches and/or if they have become more abundant than native plants that were historically present late in the season.…”
Section: Discussionmentioning
confidence: 94%
“…Ecological surveys may be fairly resource intensive as compared with other collection efforts, yet may add substantial value to ongoing biodiversity inventories. In turn, ecological research can benefit from the baselines established by historical biodiversity datasets ( Marliave et al 2011 , Marliave et al 2018a , Marliave et al 2018b , Simon et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…We sampled bumble bees as part of an ecological study investigating the impact of seasonal drought on plant-pollinator communities (Simon et al 2021). Bumble bees were collected using blue vane traps (Stephen and Rao 2005) systematically distributed across the landscape in a 2 × 2 factorial study design contrasting dry versus wet, and disturbed versus undisturbed, site conditions.…”
Section: Bumble Bee Sampling and Analysismentioning
confidence: 99%